2022
DOI: 10.3390/v14122826
|View full text |Cite
|
Sign up to set email alerts
|

Global Infection Rate of Rotavirus C during 1980–2022 and Analysis of Critical Factors in the Host Range Restriction of Virus VP4

Abstract: Information on rotavirus C (RVC) infection is lacking, partly because the prevalence of RVC among humans and animals worldwide is undefined. Data on the characteristics of the P genotype among RVC strains are also required. We performed systematic searches on the infection rates of RVC since 1980 based on the literature and gene sequences of the PubMed and GenBank databases. A phylogenetic tree of VP4 genes was constructed to evaluate the distribution of the P genotype of RVC from various hosts. The specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…Also, in phylogenetic trees, RVK amino acid sequences generally clustered together with RVC sequences, indicating a close phylogenetic relationship of both viruses. RVC has been frequently detected in diseased humans ( Zhao et al., 2022 ), but it is increasingly identified as an important pathogen in pigs ( Theuns et al., 2016 ) and with lower detection rates also in other animal species ( Otto et al., 2015 ). The relationship of RVK with RVC was evident for all virus proteins, with the exception of NSP4, which showed very low sequence identities and a different branching in phylogenetic trees.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in phylogenetic trees, RVK amino acid sequences generally clustered together with RVC sequences, indicating a close phylogenetic relationship of both viruses. RVC has been frequently detected in diseased humans ( Zhao et al., 2022 ), but it is increasingly identified as an important pathogen in pigs ( Theuns et al., 2016 ) and with lower detection rates also in other animal species ( Otto et al., 2015 ). The relationship of RVK with RVC was evident for all virus proteins, with the exception of NSP4, which showed very low sequence identities and a different branching in phylogenetic trees.…”
Section: Discussionmentioning
confidence: 99%
“…Group C has also been linked to sporadic cases of acute diarrhea among humans, worldwide. Zhao et al (2022) reported that the infection rates of rotavirus C in humans has decreased from 3% before 2009 to 1%, whereas the infection rates in animals increased from 10% to 25% [86].…”
Section: Rotavirusmentioning
confidence: 99%
“…Compared to RVB and RVC, RVA is considered to be the most predominant rotavirus due to its high detection rate in different pig herds [ 4 , 8 ]. Porcine RVC has been identified in many countries around the world [ 9 , 10 , 11 , 12 , 13 , 14 ]. After 2009, the prevalence of RVC infection in animals increased from 10% to 25% [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Porcine RVC has been identified in many countries around the world [ 9 , 10 , 11 , 12 , 13 , 14 ]. After 2009, the prevalence of RVC infection in animals increased from 10% to 25% [ 14 ]. In recent years, an increasing number of countries have reported high positivity rates of porcine RVC.…”
Section: Introductionmentioning
confidence: 99%